Emerging of Pseudo-Sustainability As A Result of Hegemony in Sustainability Reporting: An Imaginary Research Dialogue - Iqbal Lhutfi (Jurnal Pendidikan Akuntansi & Keuangan, 2023)
This research aims to uncover the pseudo-sustainability phenomenon that occurs due to regulatory hegemony from western capitalism over developing countries. This research is an imaginary dialogue between two scholars: Senior and Junior Researchers. Postmodernism is utilised to examine the discussion and to stimulate the researcher’s imagination. Sustainability reporting is made not for its original purpose as a form of social and environmental responsibility but focuses on public impressions and tools for public relations to attract more investors and enhance the company's reputation. The company has tried to make the best possible sustainability reporting to get awards and recognition to pursue good corporate governance impressions. This study emphasises how the hegemonic penetration of western capitalism has changed the regulatory framework in developing countries regarding sustainability reporting. This study contributed to uncovering the current issues regarding implementing sustainability reporting.